Efforts to increase Perisai Diri athletes’ agility, speed, balance and flexibility components through shuttle run, zigzag run, and formation of 8 training method - Carles Nyoman Wali; Martina Dewi Lengo; Lukas Dairo Bili; Wilhelmina Olok; Matheos Jerison Boru; Dixon E. M. Taek Bete (Jurnal Keolahragaan, 2023)
The biomotor component is an important factor for an athlete, especially athletes from the Perisai Diri martial arts school, to achieve achievements in a competition. Agility, Speed, Flexibility and Balance are four biomotor components that are very dominantly used in the training process and are often used by martial art athletes in competitions. The aim of this research was to find out shuttle run, zigzag run, and formation of 8 training method influence agility, speed, flexibility, and balance in pencak silat athletes. This research is quantitative research, with a quasi-experimental design of three balanced treatments. The sample in this research was 45 athetes from the 80 total athletes in population that selected by purposive sampling, devided in 3 groups, each group consisting of 15 athletes. Agility, speed, balance, and flexibility obtained with a valid and reliable instrument. The data analysis used in this research is the Wilcoxon test and the Kruskal Wallis test. To measure improvement using different means. The standard significance of sat is p=0.05 (5%). The results of the research prove that there is a significant comparison between shuttle running, zigzag running, zigzag running with a combination of 8 numbers, for agility and speed (p0.05), shuttle running is useful for improving balance and speed, zig-zag running is useful for improve dexterity and zigzag combines 8 figures which are useful for increasing flexibility. It can be concluded that there were significant differences between alternating training, zigzag running, and figure 8 formation running, especially in agility and speed. The back and forth running training method is useful for increasing balance and speed, the zigzag running training method is useful for increasing agility, and the figure 8 formation running method is useful for increasing flexibility.